1988
DOI: 10.1148/radiology.167.2.3357962
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve dysfunction in thyroid eye disease: CT.

Abstract: Optic nerve dysfunction in thyroid eye disease is thought to be due to compression of the optic nerve by enlarged extraocular muscles near the orbital apex. High-resolution computed tomography (CT) scans of 78 orbits of 31 patients with thyroid eye disease were reviewed. Axial scans alone were inadequate for demonstrating compression of the optic nerve. With a coronal reformatted scan from the axial scans, a muscular index was devised and measured to reflect extraocular muscle impingement on the optic nerve. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
102
1
14

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 0 publications
6
102
1
14
Order By: Relevance
“…Besides, previous histologic studies in patients with chronic Graves orbitopathy have demonstrated more pronounced axonal loss at the apical segments of the optic nerve. 9 As previously reported by other investigators, 4,5,8 we also found robust correlation between the degree of muscular enlargement and the presence of ON (P Ͻ .0005, Table 1). However, the degree of muscular enlargement at which ON occurs is less clear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Besides, previous histologic studies in patients with chronic Graves orbitopathy have demonstrated more pronounced axonal loss at the apical segments of the optic nerve. 9 As previously reported by other investigators, 4,5,8 we also found robust correlation between the degree of muscular enlargement and the presence of ON (P Ͻ .0005, Table 1). However, the degree of muscular enlargement at which ON occurs is less clear.…”
Section: Discussionsupporting
confidence: 90%
“…1,3 Various imaging features have been associated with the diagnosis of optic neuropathy, such as the degree of enlargement of the extraocular muscles, volumetric increase in orbital fat, radiologic evidence of apical optic nerve compression, and the presence of intracranial fat prolapse. [4][5][6][7][8] To our knowledge, the role of the bony orbit in ON has not been directly investigated. The purpose of this study was to examine both bony orbital and soft-tissue CT characteristics associated with ON in Graves ophthalmopathy, including a novel angular assessment of orbital apex capacity, and their usefulness in the risk prediction of ON.…”
mentioning
confidence: 99%
“…1,9 Finally, our study shows that CI is more efficient at detecting DON than the linear muscle index described by Barrett et al 10 In their study, a muscle index of 67% or greater indicated compressive neuropathy and had a diagnostic sensitivity of 67%. 10 In a previous study using MDCT to determine the sensitivity and specificity of the muscle index in a similar set of patients, we found that a muscle index of 60% provided the best combination of sensitivity/specificity (79% and 72%, respectively). lighted the importance of using both extraocular muscle enlargement and bony orbit anatomy to predict DON, with narrow bony orbits found to be an independent predictor of DON.…”
Section: Discussionsupporting
confidence: 51%
“…The theory is based mostly on CT imaging studies confirming the presence of orbital apex crowding in most patients with DON. 10,12,13,18,19 Because of its great importance in DON, apical crowding is quantified with a score first described by Nugent et al 15 and reproduced by many other authors, 1,3,7,9,16 which grades the effacement of the perineural fat as 0 (none), 1 (up to 25%), 2 (25%-50%), or 3 (greater than 50%). 15 Using this method, Nugent et al found severe apical orbital crowding (grade 3) in 12 of 18 orbits with DON but in only 16 of 124 orbits without DON.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation